AL-AMANAH DALAM PERSPEKTIF AL-QUR’AN - Ahmad Deski (STAI Darul Quran Payakumbuh, 2016)
Al- Qur’an is the guide human being in running life in the world. It does not only talk about faith and ibadah but also a lot of problems faced by human beings during the world. Allah delivers The Quran in Arabic. Each word of its has a very deep meaning to study. Then in this research, the researcher discusses the meaning of al Amanah. In the Quran, the word Amanah is repeated by God as many as forty-two times. The word Amanah, itself explains about humans’, prophets’ and the Angel of Jibrail alaihissalam’s characters. Besides, it also tells about gifts (enjoyment) received by obeyed men to Allah. Someone’s (servant) Amanah to Allah and His prophet is to do what He orders and not to do what is prohibited. Amanah to Allah’s prophet is by applying for his message and order, and not to against his shari’ah. Whoever runs Allah’s amanah, their nations will be avoided from His punishment. Amanah is the character of prophets in conveying Allah’s risalah in order to make human beings believe in the only One God, Allah, and obey all of what He instructs to them.